Design of CFST column-to-foundation/cap beam connections for moderate and high seismic regions. (1st September 2016) - Stephens, Max T.; Lehman, Dawn E.; Roeder, Charles W.
Highlights: A ductile concrete filled steel tube (CFST) connection is introduced. A large experimental program to evaluate connection performance and is discussed. Experimental results are used to develop design expressions for the connection. The design expressions are demonstrated in a design example. Comparisons are drawn between the CFST design and a more traditional RC design. Abstract: Seismic design of new bridges requires strength, stiffness and stable inelastic cyclic deformation capacity. In addition, rapid construction and rapid return to service after an earthquake are desired. Recent research demonstrates that circular concrete filled steel tubes (CFSTs) satisfy these diverse requirements. CFSTs are composite elements consisting of steel tubes with concrete infill. CFST columns offer larger strength and stiffness than conventional reinforced concrete bridge piers. Under seismic loading, CFSTs undergo reversed cyclic loading, and robust connections capable of sustaining cyclic lateral load demands, while minimizing damage and degradation, are required. This research project investigates foundation and cap-beam connections for these bridge applications. Several connections have been investigated, but the embedded ring CFST connection is the focus of this work. This connection develops the full strength, stiffness and ductility of the CFST bridge pier. The connection permits accelerated bridge construction and it sustains minimal damage during large inelastic deformations during earthquake loading. Results from the experiments were used to develop practical design expressions, which are presented here, and a design example is included to facilitate the implementation of the research results into practice.